Force Majeure and frustration of contract from Malaysian Civil Law and Shariah Law Perspective - Ismail, Suzi Fadhilah (2021)
This is the slides of the presentation made during the International Conference on Family Law, Family Justice and Maqasid al-Shariah (ICFL 2021) held on 9-10 Feb 2021